Bone marrow evaluation for pediatric patients. Issue 3 (17th April 2013) - Proytcheva, M.
Summary: Due to the immaturity of the hematopoietic system at birth and different oxygenation and immune response needs of the growing organism, the bone marrow composition at birth and early infancy differs as compared to older children and adults. These age‐related differences, while generally recognized, are not well known to the world of hematopathology. The purpose of this article is to address the current limitation of the literature by reviewing the bone marrow ontology, its composition at birth, and the changes occurring during early infancy, and to compare these findings to adults. The review also provides a useful framework for bone marrow examination in children.